Akibat Hukum Penetapan Pengakuan Anak Diluar Nikah Studi Putusan Nomor 12/Pdt.P/2023/Pn Wng - Rizki Rizki; Dani Josi Sipahutar (Jurnal Hukum Lex Generalis, 2025)
This research examines the legal implications of the acknowledgment of illegitimate children within the context of the Indonesian legal system, focusing on the analysis of Decision Number 12/PDT.P/2023/PN.Wng. The background of this study arises from the phenomenon of illegitimate children who often do not receive equivalent legal status, resulting in discrimination within society. The purpose of this research is to understand the legal considerations of the judge in the petition for acknowledgment of the child and the legal consequences of such acknowledgment. This study employs a normative legal method with a descriptive-analytical approach to analyze primary and secondary legal materials. The findings indicate that the acknowledgment of an illegitimate child can change the child's status from illegitimate to recognized, although there are still social and legal challenges that must be addressed. This research underscores the importance of more comprehensive regulations regarding the acknowledgment of illegitimate children to protect their rights within the Indonesian legal system.